Communality in microbial stress response and differential metabolic interactions revealed by time‐series analysis of sponge symbionts. (7th March 2022) - Taylor, Jessica A.; Díez‐Vives, Cristina; Nielsen, Shaun; Wemheuer, Bernd; Thomas, Torsten
Summary: The diversity and function of sponge‐associated symbionts is now increasingly understood; however, we lack an understanding of how they dynamically behave to ensure holobiont stability in the face of environmental variation. Here, we performed a metatransciptomic analysis on three microbial symbionts of the sponge Cymbastela concentrica in situ over 14 months and through differential gene expression and correlation analysis to environmental variables uncovered differences that speak to their metabolic activities and level of symbiotic and environmental interactions. The nitrite‐oxidizing Ca . Porinitrospira cymbastela maintained a seemingly stable metabolism, with the few differentially expressed genes related only to stress responses. The heterotrophic Ca . Porivivens multivorans displayed differential use of holobiont‐derived compounds and respiration modes, while the ammonium‐oxidizing archaeon Ca . Nitrosopumilus cymbastelus differentially expressed genes related to phosphate metabolism and symbiosis effectors. One striking similarity between the symbionts was their similar variation in expression of stress‐related genes. Our time‐series study showed that the microbial community of C. concentrica undertakes dynamic gene expression adjustments in response to the surroundings, tuned to deal with general stress and metabolic interactions between holobiont members. The success of these dynamic adjustments likely underpins the stability of the sponge holobiont and may provide resilience against environmental change.